1990
DOI: 10.1111/j.1095-8649.1990.tb02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology of carpione, Salmo carpio L., an endemic species of Lake Garda (Italy)

Abstract: Biological and ecological aspects of Lake Garda carpione, Salmo carpio L., are reported. This study reports lower catches and it is suggested that fewer carpione are now in this lake. Opercula and scales have been used for ageing fish and determining the growth rates. Life expectancy does not exceed five winters. Males became sexually active at 2 years ( = winters) of age and females at 3 years of age, however, full spawning capability is achieved only in the following year. Our data confirm that carpione have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Furthermore, derived populations of the S. trutta lineages spawn in the littoral, sublittoral and profundal zones of lakes in diverse regions such as the Italian Peninsula, Caucasus, Balkans and Maghreb (e.g. Doadrio, Perea, & Yahyaoui, ; Melotto & Alessio, ; Savvaitova & Petr, ; Sell & Spirkovski, ).…”
Section: Interspecific Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, derived populations of the S. trutta lineages spawn in the littoral, sublittoral and profundal zones of lakes in diverse regions such as the Italian Peninsula, Caucasus, Balkans and Maghreb (e.g. Doadrio, Perea, & Yahyaoui, ; Melotto & Alessio, ; Savvaitova & Petr, ; Sell & Spirkovski, ).…”
Section: Interspecific Comparisonsmentioning
confidence: 99%
“…Frequencies were determined qualitatively based on our assessment of the 350+ manuscripts read in the preparation of this review and paralleled the scoring system of Klemetsen (2013) Maghreb (e.g. Doadrio, Perea, & Yahyaoui, 2015;Melotto & Alessio, 1990;Savvaitova & Petr, 1999;Sell & Spirkovski, 2004).…”
mentioning
confidence: 99%
“…These introductions may have a major impact on local diversity, as they are carried out by organised fishing associations, which re-stock local populations of target species using non-native animals. The impoverishment of phenotypic and genetic diversity is a known consequence of these activities in European salmonids [6] , [7] , where local populations can represent divergent lineages, potential endemic taxa [8] , [9] . Actions should be taken to counteract extinction of endemic taxa and populations because of stocking with non-native individuals.…”
Section: Introductionmentioning
confidence: 99%
“…carpio is supported by the phylogenomics study of Hashemzadeh Segherloo et al (2021). Analyses of mtDNA and nDNA sequences, together with microsatellite data, (Gratton et al, 2014; Meraner & Gandolfi, 2018) showed no evidence of population substructure within carpione in spite of the fact that there are two spawning periods, December to February, and July to August (Melotto & Alessio, 1990). In addition, no significant difference in the proportion of sibship relationships within and between these winter and summer spawning groups was observed and it would appear that individuals are plastic with respect to spawning time with possible biannual spawning (Meraner & Gandolfi, 2018).…”
Section: Occurrence Of Sympatric Eurasian Trout Populationsmentioning
confidence: 99%
“…In addition, no significant difference in the proportion of sibship relationships within and between these winter and summer spawning groups was observed and it would appear that individuals are plastic with respect to spawning time with possible biannual spawning (Meraner & Gandolfi, 2018). Their diet is mainly zooplankton (principally Bythotrephes longimanus ) in the summer with benthic crustaceans (Crustacea) and chironomid larvae in the winter (Melotto & Alessio, 1990).…”
Section: Occurrence Of Sympatric Eurasian Trout Populationsmentioning
confidence: 99%